1997
DOI: 10.1177/154596839701100103
|View full text |Cite
|
Sign up to set email alerts
|

Treadmill Training with Partial Body Weight Support: Influence of Body Weight Release on the Gait of Hemiparetic Patients

Abstract: Objective: To investigate the effect of body weight support on the gait of hemiparetic subjects walking on a treadmill. Design: Survey. Patients: Eleven nonambulatory hemiparetic subjects. Methods: Subjects walked on the treadmill with full weight bearing and with 15%, 30%, 45%, and 60% body weight support at constant walking velocity. Cycle parameters, symmetry ratios, and the kinematic EMG of several lower limb muscles of the affected leg were recorded. Video-analysis served for assessment of posture and hip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
88
3
4

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(99 citation statements)
references
References 11 publications
4
88
3
4
Order By: Relevance
“…12,13 Loading and unloading in the correct rhythm and hip extension during terminal stance phase were the major peripheral drives. [14][15][16] One of the disadvantages of treadmill training was the effort for up to three therapists in lifting the paretic limbs, promoting hip extension, and assisting lateral weight transfer; this limits its use in routine clinical practice. To reduce the physical effort required of therapists, Hesse and Uhlenbrock designed an electromechanical gait trainer.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Loading and unloading in the correct rhythm and hip extension during terminal stance phase were the major peripheral drives. [14][15][16] One of the disadvantages of treadmill training was the effort for up to three therapists in lifting the paretic limbs, promoting hip extension, and assisting lateral weight transfer; this limits its use in routine clinical practice. To reduce the physical effort required of therapists, Hesse and Uhlenbrock designed an electromechanical gait trainer.…”
Section: Introductionmentioning
confidence: 99%
“…The GT Handbook suggested a maximum BWS of 35 percent for nonambulatory patients with hemiparesis and a maximum of 10 percent in patients walking with aid, including support [19]. Furthermore, clinical studies have recommended BWS limits of 30 percent on the treadmill [12] and 40 percent on the Lokomat ® [23] for maintaining the activity of antigravitational muscles. In contrast, a review on treadmill parameter selection stated that adequate support was 35 to 50 percent [18].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, therefore, training protocols vary widely among clinical trials. Low percentages of BWS and fast WSs may activate the relevant weightbearing muscles and improve locomotor efficiency [11][12] but can overstrain patients [5]. Despite every physiotherapist's concern for selecting the maximum parameter values that each patient can achieve without discomfort, clear guidelines and/or scientific analyses of these values are still lacking, as well as knowledge of their interrelationships and their effects on over-ground walking performance.…”
Section: Introductionmentioning
confidence: 99%
“…We progressed training by increasing the speed of the gait trainer and aiming for a BWS of <20 percent body weight [23][24]. Reducing the BWS as the training progresses is important for effective and progressive activation of the lower-limb muscles and increased energy expenditure [25][26][27]. Previous studies have indicated that retraining gait with BWS leads to successful recovery of walking in patients with stroke and that progressively decreasing BWS improves walking more effectively [3,28].…”
Section: Interventionmentioning
confidence: 99%